Implications of ‘Polluter Pays Principle' in Criminal Liability of Business Actors for Environmental Pollution through Wastewater - Nugroho, Mikael Adrian Tri; Salsabilla, Tengku Marisha Alda; Saufika, Tutu Sara; Manihuruk, Tri Novita Sari; Yusuf DM, Mohammad (Reformasi Hukum, 2024)
The Polluter Pays Principle (PPP) underlies the liability of business actors related to environmental pollution through wastewater. The problem is how this principle is applied in enforcing the law against perpetrators who pollute the environment through industrial activities. This paper aims to analyze the implications and urgency of PPP implementation in the legal liability of business actors for environmental pollution through wastewater. The research method used is normative legal research. The results show that implementing PPP related to environmental pollution through wastewater in law enforcement has significant implications in criminal law. This principle encourages the responsibility of businesses for the waste generated from their activities, forcing them to consider the cost of restoring the environment and cleaning up the impacts caused by the waste. Although Law No. 32/2009 on Environmental Protection and Management provides a strong legal foundation, there are obstacles to implementing PPP, such as the legal process's length and the high proof level. To address this, legal reforms are needed that speed up the legal process, increase the capacity of law enforcement agencies, and establish clear guidelines for determining proportional sanctions